2014
DOI: 10.1186/1471-2474-15-158
|View full text |Cite
|
Sign up to set email alerts
|

Web-based therapeutic exercise resource center as a treatment for knee osteoarthritis: a prospective cohort pilot study

Abstract: BackgroundAlthough beneficial effects of exercise in the management of knee osteoarthritis (OA) have been established, only 14 -18% of patients with knee OA receive an exercise from their primary care provider. Patients with knee OA cite lack of physician exercise advice as a major reason why they do not exercise to improve their condition. The purpose of this pilot study was to investigate use of a web-based Therapeutic Exercise Resource Center (TERC) as a tool to prescribe strength, flexibility and aerobic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 47 publications
(55 reference statements)
3
52
1
Order By: Relevance
“…In a secondary analysis of data from the Lifestyles trial, short term sleep improvement predicted long term improvements for sleep, pain, and fatigue that were not attributable to psychological benefits in persons with insomnia and joint pain (likely due to OA) (122). A web-based therapeutic exercise resource center was feasible and efficacious in improving pain, function, and self-efficacy in knee OA (123). Telephone reinforcement and negotiated maintenance contracts positively affected physical activity behavior in OA (124).…”
Section: Resultsmentioning
confidence: 99%
“…In a secondary analysis of data from the Lifestyles trial, short term sleep improvement predicted long term improvements for sleep, pain, and fatigue that were not attributable to psychological benefits in persons with insomnia and joint pain (likely due to OA) (122). A web-based therapeutic exercise resource center was feasible and efficacious in improving pain, function, and self-efficacy in knee OA (123). Telephone reinforcement and negotiated maintenance contracts positively affected physical activity behavior in OA (124).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies met our eligibility criteria for objective 1, review of exercise prescriptions (figure 1). 28 29 38–83 Twenty-three RCTs compared an aerobic exercise group to a non-exercising control group, 15 RCTs compared groups completing different types of exercise and 11 studies compared outcomes before and after aerobic exercise in one group. Fourteen studies reported a marker of cardiovascular health and/or systemic inflammation and were included in various meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The IBET program used in this study was developed by Visual Health Information and a multidisciplinary team, including physical therapists, physicians and patients; details of the program have been described previously [ 26 ]. Visual Health Information did not provide any financial support for this study.…”
Section: Methodsmentioning
confidence: 99%
“…While face-to-face PT visits and other physical activity programs clearly have value, several important opportunities are associated with internet-based delivery, including the capacity for widespread dissemination at relatively low cost and convenience for users. To date little research exists on internet-based physical activity programs for individuals with OA [ 25 , 26 ], and few studies of this kind have focused on older adults who comprise a large proportion of this patient group [ 27 , 28 ]. This manuscript describes the protocol of a randomized clinical trial examining the effectiveness of an internet-based exercise training program (IBET) and standard PT for patients with knee OA, both compared to a wait list control group.…”
Section: Introductionmentioning
confidence: 99%